China in world politics : policies, processes, prospects - Kornberg, Judith F., 1954-; Faust, John R., 1930- (Boulder, Colo. : Lynne Rienner Publishers, 2005)
'This fully revised text introduces students to China's foreign policy--past and present--and the factors that may influence the country's future policy agenda'--Provided by publisher.
Includes index and bibliographical references.
Keywords: China -- Foreign relations -- 1976-; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-